Nanocarriers for methotrexate delivery/codelivery in the frame of cancer diagnostics and treatment: a review - Mukhtar, Mahwash; Ezra Manicum, Amanda-Lee; Shojaei Barjouei, Masoumeh; Eshaghi Malekshah, Rahime; Behzadmehr, Razieh; Rahdar, Abbas; Ghotekar, Suresh; Baino, Francesco (Frontiers in Biomaterials Science, 2023)
Cancer is one of the most life-threatening family of diseases that cause death worldwide. As a highly researched and successful therapeutic agent, methotrexate (MTX) treats many solid tumours, hematologic malignancies, and autoimmune illnesses. Despite many benefits, methotrexate induces drug resistance and limits plasma half-life due to its poor pharmacokinetics. The variable biological availability have prompted researchers to investigate innovative delivery strategies for enhancing its therapeutic qualities. To develop more suitable methotrexate formulations, nanoparticles (NPs) have recently gained a significant interest. A wide range of nanoparticles, including polymer-based nanoparticles, carbon-based nanoparticles, lipid-based nanoparticles, as well as inorganic nanoparticles, can be deliver cancer chemotherapeutics such as methotrexate. Loading methotrexate into NPs can provide a delivery system that has shown great promise to carcinoma therapy. In this review, we will describe the feasibility of NP-based strategies to deliver methotrexate in cancer therapy, outlining the current state of the art and the challenges/promises for the future.